Teaching English overseas : - McKay, Sandra Lee (Oxford University Press, 1997)
This book makes several assumptions about teaching overseas. It is divided into two parts. The first focuses on the ways in which socio, political, economic, and cultural factors can influence the overseas classroom. The second investigateshow a country's educational and institutional structures can effect language teaching. The book includes questions for discussion and small-scale research, a glossary, and an index